Perlindungan Hukum Pelaku Usaha Atas Penggunaan Economic Evidence Sebagai Alat Bukti Petunjuk Dalam Hukum Persaingan Usaha di Indonesia - Melkisedek Vajar Silaban; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Differences in perspective on the position of economic evidence as evidence in business competition law in Indonesia at the level of the Business Competition Supervisory Commission, District Court, to the Supreme Court occur or are caused by no conformity of regulations related to the use of evidence in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Business Competition resulting in frequent KPPU decisions being canceled. The study entitled "Legal Protection of Business Actors over the Use of Economic Evidence as Proof of Guidance in Business Competition Law in Indonesia", has the problem formulation of how the position of economic evidence as evidence evidence of instructions in resolving business competition disputes in Indonesia and how is the legal protection of business actors for the use economic evidence as evidence of instructions in business competition law.The purpose of this thesis is: first, to find out the position of economic evidence as evidence evidence in the resolution of business competition disputes in Indonesia. Second, to find out the legal protection of business actors for the use of economic evidence as evidence evidence in business competition law in Indonesia. This type of research is normative legal research or can also be called doctrinal legal research. In this normative study the researcher conducts research on the principles of law. This research is a descriptive analysis which describes and analyzes the problems raised that aim to describe concretely about the legal protection of business actors for the use of economic evidence as evidence evidence in business competition law in Indonesia.From the results of the research there are two main issues that are concluded, first, in terms of the position of economic evidence as evidence evidence for its use does not yet have a clear and firm regulation in the Act. Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition Secondly, in terms of providing legal protection for business actors in order to provide legal certainty it is necessary to make a revision related to the regulation regarding the handling of business competition cases at the KPPU level, the District Court, to the Supreme Court to prevent dualism law. And regarding the concept of proving indirect evidence in resolving business competition disputes needs to be regulated firmly and clearly in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition so that it can become a reference for KPPU, District Courts, and Supreme Court institutions in handling business competition casesKey words: Legal Protection – Economic Evidence – Competition Law